Genetic diversity of wheat (Triticum aestivum L.) genotypes with grain zinc and iron content for yield and its attributing traits - Sharna, Shanzida Khan; Anwar, Md. Tahsinul; Akhter, Shirin; Mohiuddin, K. M.; Sagor, G. H. M. (Journal of Phytology, 2024)
Wheat (Triticum aestivum L.) is crucial for global food security, providing essential calories for about one-third of the world’s population and a great source of micronutrients like zinc (Zn) and iron (Fe). This study focuses on the screening of thirty wheat germplasms for Zn and Fe content, and their association with yield and related traits. Analysis of variance showed significant variation among the genotypes for all studied traits including Zn and Fe content. The phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were very close for micronutrient indicating fruitful for selection of these traits, whereas great differences for yield and yield attributing traits. High heritability coupled with high genetic advance was also observed for Zn and Fe content, but low for yield per plant. Genotype BAW897 and DSN117 for Zn, BAW1006 and SADH-22 for Fe and BAW1006 and Sonalika for yield were selected based on the mean performance, and BAW667 was best considering all three traits, suggesting their suitability and adaptability for cultivation to fulfil the agricultural demand. Zn and Fe content showed negative associations with canopy temperature, chlorophyll content yield and its different contributing characters. Principal Component Analysis revealed that zinc had a positive value in PCA1, iron showed a positive value in PCA2, and total yield was positively associated with PCA2, with the first five components explaining 77.1% of the cumulative variance. The thirty genotypes were clustered in four major groups, having maximum number in cluster 1 and minimum in cluster 4. Cluster 1 consists of the most promising genotypes having higher micronutrient content and high yielding ability. The identified genotypes can be utilized in forthcoming breeding to ensure both food and nutritional security in Bangladesh.